PENDIDIKAN POLITIK DAN HUKUM PERSEPEKTIF AL-QURAN DAN HADIS - Yahanan; Andika Jun Priadi; Aldira Salsabilla; Ananda Pane; Khalid Jamuri Harahap; Sultoni; Fadhly Yassin Tanjung; Wardi; Mhd Dedi Hcomaludin Jamil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Filtration is an important separation Islam is a comprehensive religion that regulates not only ritual worship but also all aspects of human life, including national affairs, power, government, and political education (fiqh siyasah). This study aims to formulate the core principles of Islamic political law and the channels of political education from the perspective of the Qur'an and Hadith. This formulation is crucial to ensure that dynamic political developments remain aligned with Shari'ah norms and are capable of building a political culture of a civilized society. Employing a library research method, this study formulates six fundamental principles of Islamic political law: sovereignty, justice, consultation (syura) and consensus (ijma'), equality, reciprocal rights and obligations between the state and the people, and amar ma'ruf nahi munkar. In the Qur'an, power is conceptualized through the terms Sulthan (physical ability/coercion), Mulk (ownership right), and Hukm (organizing order). This study emphasizes that leadership is a sacred trust and responsibility to ensure public welfare without tyranny or deception. Furthermore, to build a political culture of a civilized society, political education must be effectively channeled through two avenues: formal education in schools and community education through political party cadre development and socialization.